2008
DOI: 10.1369/jhc.2008.951061
|View full text |Cite
|
Sign up to set email alerts
|

Periostin Is Expressed in Pericryptal Fibroblasts and Cancer-associated Fibroblasts in the Colon

Abstract: S U M M A R Y Periostin is a unique extracellular matrix protein, deposition of which is enhanced by mechanical stress and the tissue repair process. Its significance in normal and neoplastic colon has not been fully clarified yet. Using immunohistochemistry and immunoelectron microscopy with a highly specific monoclonal antibody, periostin deposition was observed in close proximity to pericryptal fibroblasts of colonic crypts. The pericryptal pattern of periostin deposition was decreased in adenoma and adenoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
115
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 120 publications
(135 citation statements)
references
References 35 publications
18
115
1
Order By: Relevance
“…The expression of periostin has been shown to play a role in colon cancer progression by influencing cell growth, invasion, and apoptosis (7,23,24). In the present study, we investigated both serum levels and expression of periostin in CRC tissue samples, and analyzed potential correlations between serum periostin levels and certain clinical characteristics of the tumor.…”
Section: Discussionmentioning
confidence: 96%
“…The expression of periostin has been shown to play a role in colon cancer progression by influencing cell growth, invasion, and apoptosis (7,23,24). In the present study, we investigated both serum levels and expression of periostin in CRC tissue samples, and analyzed potential correlations between serum periostin levels and certain clinical characteristics of the tumor.…”
Section: Discussionmentioning
confidence: 96%
“…Kikuchi et al (31) identified the connection between periostin expression and colorectal crypt fibroblasts and infiltrating fibroblasts of the tumor tissue. Periostin-mediated induction of fibroblasts resulted in an increase in the number of HCT 116 colon cancer cells in co-culture (31).…”
Section: Periostin In Colorectal Cancermentioning
confidence: 97%
“…Full-length periostin is a secreted 90-kDa disulfide-linked protein composed of a typical signal sequence followed by a cysteine-rich EMI domain (believed to be important in multimerization), a tandem repeat of four fascilin-like (FAS1) domains-an evolutionarily conserved domain considered important in adhesion-and a variable C-terminal region (2)(3)(4)(5). Periostin is considered a matricellular protein with expression confined to cells in connective tissues, including the periodontal ligament, tendons, heart valves, myocardium, skin, and bone (6,7). Despite lacking an RGD domain, periostin is thought to interact with multiple integrins, including αVβ3, αVβ5, and α6β4, to initiate a variety of biologic effects including cell proliferation, cell migration, epithelial to mesenchymal transformation, modulation of the biomechanical properties of connective tissues, and regeneration of cardiac myocytes after injury (4,8,9).…”
Section: Mmp-9mentioning
confidence: 99%